2014
DOI: 10.1016/j.jcrs.2013.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule opacification with 3 intraocular lenses: 12-year prospective study

Abstract: After 12 years, there was no difference in PCO or overall survival without capsulotomy between the acrylic IOL and the silicone IOL. The HSM PMMA IOL had a significantly higher PCO fraction than the silicone IOL and lower overall survival than the acrylic IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
1
30
1
2
Order By: Relevance
“…Few papers report PCO evaluation more than four years after surgery. Ronbeck et al 8 reported that hydrophobic acrylic IOLs delayed PCO development, with a median time of survival without Nd:YAG capsulotomy of 108 months. PCO rates were reported for approximately 50% of the patients approximately 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Few papers report PCO evaluation more than four years after surgery. Ronbeck et al 8 reported that hydrophobic acrylic IOLs delayed PCO development, with a median time of survival without Nd:YAG capsulotomy of 108 months. PCO rates were reported for approximately 50% of the patients approximately 10 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that indeed the silicone IOL with a round edge was as good as the acrylic IOL with a sharp edge in the prevention of PCO during the long-term follow-up. 18 …”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, in a long-term follow-up, a sharp optic edge design that did not result in diminution of PCO was reported with the use of hydrophobic acrylic IOLs when compared with silicone IOLs without a sharp-edged optic. 12 , 18 Further studies of silicone IOLs in this regard would be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confirmed that HSM PMMA have good uveal biocompatibility in uveitic patients. [ 43 44 ] However, Rønbeck and Kugelberg[ 45 ] made a 12-year prospective study on PCO rate of HSM PMMA, silicone, and hydrophobic acrylic IOL and concluded that HSM PMMA IOL had a significantly higher PCO rate. The different PCO rates with different IOL materials showed that both “material surface factor” and “design factor” were important.…”
Section: H Eparin-surface-modified P Olymentioning
confidence: 99%